A Reflection about the Mathematics Modelling in the Context of the Critical Mathematical Education Uma Reflexão sobre a Modelagem Matemática no Contexto da Educação Matemática Crítica - Otávio Roberto Jacobini; Maria Lucia Wodewotzki (Universidade Estadual Paulista, 2008)
With this study we intend to discuss the possibilities for inserting modeling in the context of Critical Mathematical Education, approaching reflections that can contribute to the student's political growth. In the one hand, this political growth is associated with political awareness resulting from the student's actions in investigations related to all themes from modeling projects, in discussions that come with results and in debates about the reach of these results and their social consequences. On the other hand, this growth is associated with political action that becomes real due to the student's involvement with the community. We conclude this study by indicating that the student's growth process should be seen as way of mathematical alphabetizing that goes beyond the exclusivity of just learning mathematics for its own sake, but valuing the formation of a critical student, whoknows the problems in society and is aware of the importance of his contribution to the community. Key-words: Mathematical Modelling. Critical Mathematics Education. Political Action. Com este estudo buscamos discutir as possibilidades de inserção da modelagem no contexto da Educação Matemática Crítica, abordando reflexões que possam contribuir para o crescimento político do estudante. Esse crescimento político associa-se, de um lado, com a conscientização política resultante da sua atuação em investigações diretamente relacionadas com os temas dos projetos de modelagem, nas discussões que acompanham os resultados obtidos e no debate sobre o alcance desses resultados e sobre as conseqüências sociais do trabalho realizado. De outro lado, esse crescimento associa-se com uma ação política que se concretiza por meio do envolvimento do estudante com a comunidade. Concluímos este estudo indicando que o processo de crescimento político dos estudantes deve ser pensado como uma forma de alfabetização matemática que, extrapolando a exclusividade do foco da aprendizagem na matemática em si, valorize a formação de um estudante crítico, conhecedor dos problemas que afligem a sociedade e consciente da importância da sua participação na comunidade. Palavras-chave: Modelagem Matemática. Educação Matemática Crítica. Ação Política.